2021
DOI: 10.1111/obr.13224
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety of naltrexone and bupropion therapy: Systematic review and meta‐analyses

Abstract: Summary Despite being approved for clinical use, evidence of cardiovascular safety (CV) is lacking for treatment with bupropion, naltrexone, or their combination (B‐N). The purpose of the study is to determine the relationship between these treatments and the risk of major cardiovascular adverse events (MACE). Phase 3 randomized clinical trials (RCT) evaluating bupropion, naltrexone, or B‐N versus control with reported incidence of MACE. The meta‐analysis included 12 RCTs, 69% for weight loss and 29% for smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“… 108 The CV safety was recently evaluated in a network meta-analysis of phase 3 trials on NB, using each drug separately or in combination, for smoking cessation or for weight management, and showed no increased risk of major adverse cardiovascular events, defined as MACE. 109 …”
Section: Resultsmentioning
confidence: 99%
“… 108 The CV safety was recently evaluated in a network meta-analysis of phase 3 trials on NB, using each drug separately or in combination, for smoking cessation or for weight management, and showed no increased risk of major adverse cardiovascular events, defined as MACE. 109 …”
Section: Resultsmentioning
confidence: 99%
“…Sposito et al conducted a systematic literature review and meta-analysis of Phase 3 RCTs evaluating bupropion, naltrexone, or naltrexone with bupropion, and found no significant difference in the incidence of MACE between treatment groups. 87 …”
Section: Discussionmentioning
confidence: 99%
“…Sposito et al conducted a systematic literature review and meta-analysis of Phase 3 RCTs evaluating bupropion, naltrexone, or naltrexone with bupropion, and found no significant difference in the incidence of MACE between treatment groups. 87 Diabetes, Metabolic Syndrome and Obesity: Targets and Therapy 2022: Finally, only published articles identified in accordance with the literature search protocol were included in this review. Despite extensive efforts to identify all relevant sources available through a pre-defined search strategy, with input from experts in both the product literature and systematic literature reviews, some sources with relevant information may have been overlooked or not identified for inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent adverse events reported in the RCTs with NB treatment were nausea, headache, and constipation [ 66 , 67 ]. Cardiovascular safety still needs to be investigated by a RCT, but a recent systematic review and meta-analysis found no association between the use of naltrexone, bupropion, or their combination and the incidence of major cardiovascular adverse events compared with placebo [ 70 ]. Nevertheless, patients with hypertension or other cardiovascular diseases should be aware of the small but not trivial sympathomimetic effects of bupropion, as it can increase blood pressure and heart rate [ 65 ].…”
Section: Fixed-dose Combination Of Drugs: Naltrexone Plus Bupropion A...mentioning
confidence: 99%